Colonial Economic Policies and Trade in Bangalore under the British Governor Generals’ Rule - Babu Venkatesh Prasad Gowda K.K. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
This paper examines the economic transformation of Bangalore under British colonial rule, focusing on the period spanning the nineteenth and early twentieth centuries. It analyzes how the policies enacted by the Governor-General and implemented through the Madras Presidency reshaped agrarian structures, trade flows, artisanal production, and urban economy. Using archival sources such as Madras Presidency annual reports, Mysore Gazetteers, and railway records, along with secondary scholarship on deindustrialization, urbanism, and economic history, the paper argues that colonial administrative interventions created a dual legacy: modernization of infrastructure and integration into global markets, accompanied by the decline of indigenous industries and the deepening of agrarian and artisanal vulnerabilities. The paper also examines the role of the Bangalore cantonment in shaping demand structures, indigenous banking in facilitating trade, and comparative perspectives with other urban centers in British India. By combining macroeconomic analysis with micro-level case studies, the research highlights the spatial, social, and economic consequences of colonial policies, providing insights into the long-term patterns that shaped Bangalore’s postcolonial development.